Low‐Temperature Remediation of NO Catalyzed by Interleaved CuO Nanoplates. (30th April 2014) - Auxilia, Francis Malar; Ishihara, Shinsuke; Mandal, Saikat; Tanabe, Toyokazu; Saravanan, Govindachetty; Ramesh, Gubbala V.; Umezawa, Naoto; Hara, Toru; Xu, Ya; Hishita, Shunichi; Yamauchi, Yusuke; Dakshanamoorthy, Arivuoli; et al.
<x xml:space="preserve">Abstract</x> A copper(II)‐oxide‐based exhaust catalyst exhibits better activity than Pt‐ and Rh‐nanoparticle catalysts in NO remediation at 175 °C. Following theoretical design, the CuO catalyst is rationally prepared; CuO nanoplates bearing a maximized amount of the active 001 facet are arranged in interleaved layers. A field test using a commercial gasoline engine demonstrates the ability of the catalyst to remove NO from the exhaust of small vehicles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>